Extraction Method and Analysis of Cannabinoids in Cannabis Olive Oil Preparations - Casiraghi, Antonella; Roda, Gabriella; Casagni, Eleonora; Cristina, Cecilia; Musazzi, Umberto Maria; Franzè, Silvia; Rocco, Paolo; Giuliani, Claudia; Fico, Gelsomina; Minghetti, Paola; Gambaro, Veniero (Planta Medica, 2018)
Recently, an increasing number of pharmacists had to supply medicinal products based on Cannabis sativa L. (Cannabaceae), prescribed by physicians to individual patients. Cannabis olive oil preparation is the first choice as a concentrated extract of cannabinoids, even though standardized operative conditions for obtaining it are still not available. In this work, the impact of temperature and extraction time on the concentration of active principles was studied to harmonize the different compounding methods, optimize the extraction process, and reduce the variability among preparations. Moreover, starting from the cannabis inflorescence, the effect of temperature on tetrahydrocannabinolic acid decarboxylation was evaluated. For the analysis, a GC/MS method, as suggested by the Italian Ministry of Health, and a GC/flame ionization detection method were developed, validated, and compared.
Keywords: Cannabis sativa; Cannabaceae; olive oil preparation; cannabinoids; extraction; GC/FID; GC/MS